(untitled) (Revista Educação, Artes e Inclusão, 2020)
The study attempts to discover elements of learning by practicing the right to the city through the embodiment and re-articulation of the identity of the ﬂâneuse. In this urban investigation, we will explore perspectives that emerge from the city, how they are connected to specific city sites, and how they form our becomings, having in mind the gendered division of urban life. In order to do so, we will engage in reflexive wandering and performing in the city. Learning that unfolds with this action is a bodily and sensorial process of reading the layers of public spaces in the city. As wandering implies a turn off the main road, the learning process is marked by unpredictability and meandering. It does not follow a familiar path that leads to specific learning outcomes, but involves a journey through unknown and unowned places. We aim to describe learning that evolves by wandering around the side roads of Belgrade by mapping the experiences of the three authors. The research also involves reminiscences of the wandering of women in Belgrade that we want to re-enact and document.